Post‐budburst hand finishing of winter spur pruning can delay technological ripening without altering phenolic maturity of Merlot berries. (22nd March 2020) - Allegro, G.; Pastore, C.; Valentini, G.; Filippetti, I.
Abstract: Background and Aims: Global warming can lead to technological ripening occurring in advance of phenolic maturity for red wine cultivars. This study evaluated the effect of post‐budburst winter pruning on the phenology, yield components, berry composition and phenolic maturity in Vitis vinifera L. cv. Merlot. Methods and Results: Mechanically pre‐pruned vines followed up with hand pruning during winter (Control) were compared to vines that were mechanically pre‐pruned and followed up with hand pruning after budburst when distal buds developed shoots with either three unfolded leaves (DF3) or eight unfolded leaves (DF8). Late pruning delayed budburst, flowering and, to a lesser extent, veraison. The delays were greater for DF8 than DF3 treatments. Yield decreased by about 40 and 71% in DF3 and DF8 vines, respectively, while sugar accumulation and reduction of TA were delayed by both pruning treatments. The concentration of anthocyanin and tannin and of extractable anthocyanin and tannin (of skin and seeds analysed separately) were not influenced by the DF3 treatment while tannin concentration increased in DF8 berries. Conclusions: Delaying hand pruning of mechanically pre‐pruned vines until after budburst of distal nodes can delay technological ripening without affecting the concentration of anthocyanin and tannin of berries. Yield, however, is substantially reduced. Significance of the Study: We verified the feasibility of a cost‐effective technique that can be adopted to counteract the hastening of sugar accumulation and organic acid decline caused by global warming on valuable black grapes.